STUDI KASUS: PENERAPAN EFFLEURAGE MASSAGE TERHADAP PENURUNAN AFTER PAIN PADA IBU POST PARTUM - Lestaluhu, Viqy (Jurnal Kebidanan, 2024)
The postpartum period or puerperium is the period after childbirth is complete, up to 6 weeks or 42 days. During the postpartum period, the reproductive organs will slowly experience changes to the condition before pregnancy. This process of physical change sometimes causes discomfort known as postpartum pain (afterpain). The pain or afterpain is like heartburn caused by contractions of the uterus. This afterpain lasts for 3-4 days post partum and often occurs in multiparas, because the uterus is stretched, uterine contractions tend to occur twice as often as in primiparas. One treatment that can be used to overcome this problem is by applying non-pharmacological therapy to post-partum mothers. Effleurage massage can improve blood circulation throughout the body, maintain health, help reduce pain and fatigue, stimulate the production of endorphins which function to relax the body, reduce stress hormones (cortisol), and balance the work of the body's organs and overcome fatigue. This case study describes the application of effleurage massage to a post partum mother who complained of after pain. After midwifery care was implemented, Mrs. B experienced a decrease in after pain so that the problem could be resolved.